BATIK DAN TENUN SEBAGAI JATIDIRI BANGSA - Herry Pujiharto (Ars: Jurnal Seni Rupa dan Desain, 2007)
Batik and traditional woven cloth the Indonesian cultural heritage created by skilled hands canstill compete with imported products and are considered to possess high artistic characteristics(craftsmanship). Nowadays, they retain a strong presence throughout Indonesian society reflecting thesocial changes which have occurred within society because o f technological development. The creativity andinnovation involved in producing new things represents the identity o f each region in Indonesia. Thegovernment should put their effort into increasing the awareness o f producers to include the tag "Made inIndonesia " on their products. By doing so, the government educates consumers to know and believe that theitems they wear arc the product o f their culture. Such an effort, instead o f being on its own, is a part o f broaderproduction system which forms a value-added chain. Cooperation between the upper and lower ends o f thischain can provide positive benefits. Even though the flood o f imported products is unavoidable, there isnothing to be concerned about since Indonesian consumers have benefited as well. However.; should we leaveit as it is? /4s children o f the nation, we are supposed to reflect, offer introspection and, eventually, dosomething to do something so that the local products can be accepted more by their own people.Keywords : national identity, import-focused, value-added chain